Dynamics of Vibro-Impact Systems Proceedings of the Euromech Collaquium 15–18 September 1998 - Babitsky, V. I. (Springer Berlin Heidelberg, 1999)
Main topics: - excitation, synchronisation and stabilisation of vibro-impact processes - dynamics of vibro-impact machines and technological processes - non-linear phenomena due to vibro-impact interaction of solids - synergistic effects of repeated impacts on solids and granular media - control of vibration by impacts - analytical, experimental and numerical methods for the analysis of vibro-impact systems and processes - synthesis and optimisation of vibro-impact systems - measurements of vibro-impact processes